2012
DOI: 10.2965/jwet.2012.253
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contamination of Arsenic and Heavy Metals around Cho Dien Lead and Zinc Mine, Vietnam

Abstract: An onsite survey of heavy metal pollution in the environment, including tailings, soil, and water around Cho Dien mine was conducted. There is considerable amount of heavy metal pollutants, such as As, Cu, Cd, Pb, Zn, present at various levels in soil, surface water, and drinking water. Note that, most of the soil samples are being severely polluted with Pb, Zn, Cd and As. The results showed that 100% of soil samples contained Pb and Zn exceeding the Vietnamese standards. Tailings sample was found to contain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…As illustrated in Table 1, only three studies in other countries and regions reported on this subject, including studies in Vietnam, Nigeria, and Korea. The groundwater surrounding the lead-zinc mines from Vietnam contained the highest heavy metal concentrations, with a mean value of 71 mg/L among four selected studies, owing to the higher heavy metal content in soils in the vicinity of lead-zinc mines (Ha et al, 2011;Hien et al, 2012). The mean concentration of the eight heavy metals in groundwater in this study was moderate compared to those of the other three studies.…”
Section: Comparisons Of Results With Other Studiesmentioning
confidence: 55%
“…As illustrated in Table 1, only three studies in other countries and regions reported on this subject, including studies in Vietnam, Nigeria, and Korea. The groundwater surrounding the lead-zinc mines from Vietnam contained the highest heavy metal concentrations, with a mean value of 71 mg/L among four selected studies, owing to the higher heavy metal content in soils in the vicinity of lead-zinc mines (Ha et al, 2011;Hien et al, 2012). The mean concentration of the eight heavy metals in groundwater in this study was moderate compared to those of the other three studies.…”
Section: Comparisons Of Results With Other Studiesmentioning
confidence: 55%
“…With respect to pollution in drinking water, the results showed that approximately 10% of samples have lead concentrations exceeding the permitted standards in Vietnam. The problem of lead pollution in the environment has been known for many years despite intervention by the local authorities [ 15 , 17 , 18 ]. Typically, research conducted by author Nguyen Thi Thu Hien (2012) showed that the lead concentration in soil and drinking water in 3 villages in Ban Thi (Phja Khao, Ban Nhuong, and Hop Tien) was much lower than our study.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, research conducted by author Nguyen Thi Thu Hien (2012) showed that the lead concentration in soil and drinking water in 3 villages in Ban Thi (Phja Khao, Ban Nhuong, and Hop Tien) was much lower than our study. This may indicate that the accumulation of lead in the soil over time may be due to mining and production activities [ 18 ]. These findings show an alarming risk of lead contamination in children and the urgent need to have interventions for these environmental issues in these specific residential areas, in parallel with medical interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acid mine drainage (AMD) is generated at many active, closed, and abandoned mines throughout the world. AMD is a serious environmental issue in the mining industry [1][2][3][4][5][6][7][8][9], which is generally characterized by low pH and high concentrations of sulfate, heavy metals (e.g., copper (Cu), lead (Pb), zinc (Zn), and cadmium (Cd)) [10,11], and metalloids (e.g., arsenic (As), [12]). Low pH is caused by oxidation of sulfide minerals and dissolves heavy metals in the host rock.…”
Section: Introductionmentioning
confidence: 99%